INTERNET RESOURCES FOR QUALIFICATION UPGRADE, SCIENTIFIC, EDUCATIONAL AND PROFESSIONAL ACTIVITIES - MATVEYEVA, Olena V.; SHYTIKOVA, Tetiana M.; YUNAKOVSKA, Victoriia V.; VOITOVYCH, Olha V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
Objective. The article aims to familiarize with online resources, useful to librarians, scientists, teachers, and students. Methods. Overview of online resources for distance learning, qualification upgrade, scientific, educational and professional activities. Results. The description and characteristics of Internet resources for scientific, educational and professional activities is given. Conclusions. Distance learning is an important component of continuous professional development, a convenient modern format of professional improvement. The advantage of distance learning is the opportunity to learn at a convenient time and in any place. The use of modern Internet tools (including author identifiers) in your activities opens up new opportunities.